2023
DOI: 10.1177/14034948231151299
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stillbirth and preterm birth among undocumented pregnant migrant women in Denmark: A retrospective case-control study

Abstract: Aims: To examine the associations between undocumented pregnant migrant women and the risk of experiencing stillbirth or preterm birth. Methods: A retrospective case–control study based on nationwide registers from Statistics Denmark and hospital journals from the seven largest hospital wards in Denmark from 1 January 2011 to 31 December 2018. A total of 882 undocumented pregnant migrant women and 3528 matched controls (both documented migrant and non-migrant women) were included. Logistic regression models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One study from Denmark found that UMs were at a higher risk of stillbirth and preterm birth than the control group. A higher adjusted odd of experiencing stillbirth (aOR 3.50; 95% CI 1.31–9.38) and preterm birth (aOR 1.41; 95% CI 1.04–1.93) were observed among the undocumented pregnant migrant women compared with the control group ( 20 ) whereas ( 23 ), in their study uncovered no preterm deliveries (<37.0), low birth weight babies (<2,500 g), nor stillbirths. The rates were higher for preterm birth (RR 1.47, 95% CI 1.21–1.79 and RD 19.3, 95% CI 7.6–13.0 per 1,000 births), and low birth weight (RR 1.36, 95% CI 1.11–1.66 and RD 15.9, 95% CI 3.9–28.0 per 1,000 births) among UMs in Sweden compared to their Swedish counterparts ( 24 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…One study from Denmark found that UMs were at a higher risk of stillbirth and preterm birth than the control group. A higher adjusted odd of experiencing stillbirth (aOR 3.50; 95% CI 1.31–9.38) and preterm birth (aOR 1.41; 95% CI 1.04–1.93) were observed among the undocumented pregnant migrant women compared with the control group ( 20 ) whereas ( 23 ), in their study uncovered no preterm deliveries (<37.0), low birth weight babies (<2,500 g), nor stillbirths. The rates were higher for preterm birth (RR 1.47, 95% CI 1.21–1.79 and RD 19.3, 95% CI 7.6–13.0 per 1,000 births), and low birth weight (RR 1.36, 95% CI 1.11–1.66 and RD 15.9, 95% CI 3.9–28.0 per 1,000 births) among UMs in Sweden compared to their Swedish counterparts ( 24 ).…”
Section: Resultsmentioning
confidence: 97%
“…Several studies ( 13 , 15 18 ) have highlighted exactly how limited, substandard, or unavailable maternal services are for UMs and what the barriers are to accessing these services in various European countries. Some studies have gone further to explore how UMs utilise the skeletal maternal services available ( 14 , 19 ); and to investigate the experiences or maternal health outcomes of this target population ( 17 , 20 , 21 ). However, there exists a scarcity of research detailing exactly how limited access to ANC affects the pregnancy experiences of UMs living in Europe and the long-term impacts.…”
Section: Introductionmentioning
confidence: 99%